Radical and Moderate Currents of the Indonesian National Movement - Situngkir, Cindy; Silitonga, Dania Amanda Br; Lubis, Nasya Adinda Putri (Holistic Science, 2024)
In the lives of people, especially colonized people, there will always be an attempt to free themselves from the shackles of colonialism so that they can have an independent life. The aim of writing this article is to examine radical and moderate currents during the National Movement. The research method for this article is a qualitative description method with studies sourced from journals, physical and non-physical books. National movement organizations in Indonesia are divided into 3 periods, namely the formation period, the radical period and also the moderate period.